The meaning of resilience in adulthood - Franczok-Kuczmowska, Agnieszka (Kwartalnik Naukowy Fides et Ratio, 2022)
The aim of this article is to present an extensive description of resilience in adulthood in the modern times. Taking into account resilience’s definition problems, the differences and similarities between the concepts of resilience and resiliency were taken into account. The article discusses a broad definition of resilience, referring to many scientific perspectives. The conclusion is drawn that resilience should be conceptualized as a dynamic process. The meta-analysis of the relationships between the factors indicates the presence of many factors directly and indirectly related to the resilience, but only some of them are characterized by strong scientific evidence.The article reviews the literature on the importance of selected factors of resilience, especially in the context of adulthood and contemporary challenges. In the presented considerations, the mental health topic in the period of SARS-CoV-2 virus and the consequences of the global COVID pandemic in the world-wide population context should claim our attention. The wide social-economic crisis experience, as well as the high level of anxiety level that comes along society, prompts us to continue searching for resources that will act as protective factors. The ongoing war In Ukraine is also not without significance, as it leaves its mark on the daily mental functioning of both, refugees, witnesses, and individuals, who provide selfless help.The article aims to discuss the importance of resilience in adulthood in the context of health, pointing to a negative relationship with negative mental health indicators, a positive relationship with positive mental health indicators, and a relationship between resilience and personality traits. In the considerations on resilience importance, the ability of emotional disengagement, patterns of physiological reactions and the comparison of resilience to the somatic immune system were discussed. The aim of this article is also to indicate the cognitive component, namely the cognitive resilience. In this regard, the relationship between immunity and cognitive functions was discussed on the basis of experimental studies.